Hybrid Dielectric Resonator Antenna Composed of High-Permittivity Dielectric Resonator for Wireless Communications in WLAN and WiMAX - Yih-Chien Chen (International Journal of Antennas and Propagation)
The-hybrid dielectric resonator antenna consisted of a cylindrical high-permittivity dielectric resonator, a rectangular slot, and two-rectangular patches were implemented. The hybrid dielectric resonator antenna had three resonant frequencies. The lower, middle, and higher resonant frequencies were associated with the rectangular slot, rectangular patches, and dielectric resonator, respectively. Parametric investigation was carried out using simulation software. The proposed hybrid dielectric resonator antenna had good agreement between the simulation results and the measurement results. The hybrid dielectric resonator antenna was implemented successfully for application in 2.4/5.2/5.8 GHz of WLAN and 2.5/3.5/5.5 GHz of WiMAX simultaneously.